2016
DOI: 10.1080/14767058.2016.1240162
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of maternal cell contamination in amniotic fluid samples

Abstract: A significant amount of MCC is present with direct analysis of the initial few milliliters of amniotic fluid withdrawn and is not influenced by the volume of the discard sample. Our results suggest that the first few milliliters of amniotic fluid be removed and discarded when direct analysis is utilized for prenatal genetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…When we used STR detection technology to rule out maternal cell contamination, we performed two rounds of DNA analysis after confirming that there was no maternal cell contamination. Using these methods, we successfully minimized the risk of maternal cell contamination to guarantee the accuracy and reliability of the results …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we used STR detection technology to rule out maternal cell contamination, we performed two rounds of DNA analysis after confirming that there was no maternal cell contamination. Using these methods, we successfully minimized the risk of maternal cell contamination to guarantee the accuracy and reliability of the results …”
Section: Discussionmentioning
confidence: 99%
“…Using these methods, we successfully minimized the risk of maternal cell contamination to guarantee the accuracy and reliability of the results. 21 The term invasive prenatal diagnosis refers to obtaining fetal ma- In conclusion, we here conducted a systematic study of DNA-…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have revealed different incidence rates of maternal contamination in chorionic villus, miscarriage tissue or amniotic fluid samples in prenatal diagnosis [16,17]. Some of the existing studies have shown that the proportion of MCC in amniotic fluid samples is higher compared to sample types, while some other studies have indicated that the chorionic villus has higher proportion [18,19]. However, it is necessary to perform MCC detection in prenatal diagnosis regardless of these incidence variations among sample types [6,20].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of clinical speci-mens is directly related with the accuracy of high-throughput sequencing detection, while the presence of maternal cell contamination in chorionic villus, miscarriage tissue or amniotic fluid samples poses a serious analytical risk for prenatal misdiagnosis [2]. According to existing literature, the proportion of the maternal cell contamination (MCC) in amniotic fluid samples is as high as 25% [3]. However, contamination of clinical samples with maternal cells can be a potential source of error when applying high sensitivity de-tection technologies, such as high-throughput sequencing technology.…”
Section: Introductionmentioning
confidence: 99%
“…Eine relevante mütterliche Kontamination von mehr als 5 % wird nur bei blutig tingiertem Fruchtwasser beobachtet und spielt vor allem bei einer direkten Analyse, z.B. (SNP-)Array, eine Rolle [14]. In diesem Fall empfiehlt sich ein Kontaminationsausschluss.…”
Section: Amniocentese (Ac)unclassified